Thermal energy storage for nuclear power applications - Edwards, Jacob N. (Kansas State University, 2017)
Storing excess thermal energy in a storage media that can later be extracted during peak-load times is one of the better economical options for nuclear power in future. Thermal energy storage integration with light water-cooled and advanced nuclear power plants is analyzed to assess technical feasibility of different storage media options. Various choices are considered in this study; molten salts, synthetic heat transfer fluids, and packed beds of solid rocks or ceramics. In-depth quantitative assessment of these integration possibilities are then analyzed using exergy analysis and energy density models. The exergy efficiency of thermal energy storage systems is quantified based on second law thermodynamics. The packed bed of solid rocks is identified as one of the only options which can be integrated with upcoming small modular reactors. Directly storing thermal energy from saturated steam into packed bed of rocks is a very complex physical process due to phase transformation, two phase flow in irregular geometries and percolating irregular condensate flow. In order to examine the integrated physical aspects of this process, the energy transport during direct steam injection and condensation in the dry cold randomly packed bed of spherical alumina particles was experimentally and theoretically studied. This experimental setup ensures controlled condensation process without introducing significant changes in the thermal state or material characteristics of heat sink. Steam fronts at different flow rates were introduced in a cylindrical packed bed and thermal response of the media was observed. The governing heat transfer modes in the media are completely dependent upon the rate of steam injection into the system. A distinct differentiation between the effects of heat conduction and advection in the bed were observed with slower steam injection rates. A phenomenological semi-analytical model is developed for predicting quantitative thermal behavior of the packed bed and understanding physics. The semi-analytical model results are compared with the experimental data for the validation purposes. The steam condensation process in packed beds is very stable under all circumstances and there is no effect of flow fluctuations on thermal stratification in packed beds. With these experimental and analytical studies, it can be concluded that packed beds have potential for thermal storage applications with steam as heat transfer fluid. The stable stratification and condensation process in packed beds led to design of a novel passive safety heat removal system for advanced boiling water reactors.
Keywords: Nuclear power plants; Thermal energy storage; Exergy efficiency; Packed beds; Steam condensation